La risignificazione della solidarietà al tempo della pandemia (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The article aims to retrace the meanings of solidarity from the present Covid-19 pandemic. In the first section the author shows the difficulties of a philosophical-moral narrative of the contagion that requires the commitment to identify interpretative categories relevant to such a complex reality. The pandemic crisis therefore constitutes a solicitation to rethink an axiological pattern capable of implementing new practices. In the second part the author deals with the lexicon solidarity, recovers its ethical-philosophical ancestry in the multiple historical declinations, also tracing the legal and ethical-political meanings. Finally, the author shows how the pandemic "apocalypse" led to an unprecedented semantic extension of the lemma solidarity, which reconfirms its ability to be declined on the needs that history puts on the agenda.
Keywords: Solidarity; Pandemic; Covid-19; Responsibility; Ethics